2008 IEEE/ION Position, Location and Navigation Symposium 2008
DOI: 10.1109/plans.2008.4570082
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of global vehicle localization using navigable road maps and dead-reckoning

Abstract: Abstract-This paper presents a data fusion strategy for the global localization of car-like vehicles. The system uses raw GNSS measurements, dead-reckoning sensors and road map data. We present a new method to use the map information as a heading observation in a Kalman filter. Experimental results show the benefit of such a method when the GPS information is not available. Then, we propose a conservative localization strategy that relies mainly on dead-reckoned navigation. The GNSS measurements and the map in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 7 publications
(7 reference statements)
0
18
0
Order By: Relevance
“…In [5], Najjar et al propose a road-matching localization algorithm, using Belief Theory for road selection and Kalman Filtering for recursive estimation. Some other similar studies can be found in [7], [6]. These road-matching algorithms achieve good localization in a global fashion.…”
Section: Introductionmentioning
confidence: 71%
“…In [5], Najjar et al propose a road-matching localization algorithm, using Belief Theory for road selection and Kalman Filtering for recursive estimation. Some other similar studies can be found in [7], [6]. These road-matching algorithms achieve good localization in a global fashion.…”
Section: Introductionmentioning
confidence: 71%
“…International Journal of Navigation and Observation 5 to the MM problem that have been researched [26,27]. This paper focuses on three main algorithms from [31].…”
Section: Map Matchingmentioning
confidence: 99%
“…Map matching (MM) is the process of utilizing a digital road network map database to improve the predicted position errors during integration [25][26][27][28][29]. Motivated by the simplicity and drawbacks of KF, this research will focus on reducing the KF integration errors by utilizing MM.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in [2], [4], [5] make use of environment static map to improve SLAM matching confidence. A network of cooperating vehicles is explored in [6], [7] with the aim to improve localization of each vehicle.…”
Section: Introductionmentioning
confidence: 99%